2011
DOI: 10.1016/j.ccr.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Acts on the Microenvironment to Affect Breast Carcinogenesis by Distinct Mechanisms that Decrease Cancer Latency and Affect Tumor Type

Abstract: SUMMARY Tissue microenvironment is an important determinant of carcinogenesis. We demonstrate that ionizing radiation, a known carcinogen, affects cancer frequency and characteristics by acting on the microenvironment. Using a mammary chimera model in which an irradiated host is transplanted with oncogenic Trp53 null epithelium, we show accelerated development of aggressive tumors whose molecular signatures were distinct from non-irradiated hosts. Molecular and genetic approaches show that TGFβ mediated tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
156
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 46 publications
16
156
1
1
Order By: Relevance
“…Other studies have demonstrated increased TGFb signaling in response to UV irradiation [38][39][40]. Additionally, recent studies have implicated TGFb signaling in increased metastasis following ionizing radiation [41] and others have shown that ionizing radiation results in enhanced TGFb signaling from the tumor microenvironment that results in pro-carcinogenic effects [42]. Together these studies indicate that ALK5 signaling mediates DNp63a phosphorylation in response to UV irradiation.…”
Section: Alk5 Mediates Phosphorylation Of Dnp63a In Response To Ultrasupporting
confidence: 57%
See 1 more Smart Citation
“…Other studies have demonstrated increased TGFb signaling in response to UV irradiation [38][39][40]. Additionally, recent studies have implicated TGFb signaling in increased metastasis following ionizing radiation [41] and others have shown that ionizing radiation results in enhanced TGFb signaling from the tumor microenvironment that results in pro-carcinogenic effects [42]. Together these studies indicate that ALK5 signaling mediates DNp63a phosphorylation in response to UV irradiation.…”
Section: Alk5 Mediates Phosphorylation Of Dnp63a In Response To Ultrasupporting
confidence: 57%
“…The observation that UV-initiated phosphorylation of DNp63a was sensitive to A83-01 implicates ALK5 in the cellular response to stress, however, additional studies will be necessary to determine if ALK5-mediated DNp63a phosphorylation contributes to the role of TGFb signaling in promoting metastasis following ionizing radiation [41]. Similarly, it will be of significant interest to determine if the potent TGFb response of the tumor microenvironment to radiation [42] contributes to DNp63a phosphoryla- Figure 6. TGFB treatment destabilizes DNp63a in a manner that is dependent upon the kinase activity of ALK5.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by preclinical studies showing radiotherapy to reduce ER-expression in breast cancer cell-lines and rat mammary-tumors (22)(23)(24)(25), as well as to induce ER-negative breast cancer in premenopausal mice (26). Potential explanations could be: Activation of DNA-repair pathways influencing ER-expression (23); Disturbance of ERautoregulation involving micoRNA (27,28); Microenvironmental changes inducing an ERnegative stem-cell-enriched phenotype (29); and promoter-hypermethylation reducing estrogen binding-affinity and signaling (25,28).…”
mentioning
confidence: 71%
“…It is known that cells communicate and exchange information by employing classical mechanisms, such as secreting soluble factors or cell-to-cell adhesion contacts [32] . Although these classical events have been commonly thought of as the predominant modes of cell-to-cell communication, a novel type of vesicle secretion has recently received a great deal of attention [8,9,15,33] .…”
Section: Discussionmentioning
confidence: 99%